Clinical significance of procalcitonin in critically ill patients with pneumonia receiving bronchoalveolar lavage - Cheng, Yusheng; Li, Lingling; Zhang, Min; Wei, Yuqing; Lu, Zhiwei; Tu, Xiongwen (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Background: As a useful tool in intensive care units (ICU), fiberoptic bronchoscopy (FOB) may cause a deterioration of infection. This study is to investigate the clinical significance of procalcitonin (PCT) in critically ill patients with severe pneumonia receiving bronchoalveolar lavage (BAL). Methods: A retrospective case-control study was performed in a single respiratory ICU (RICU) with 6-bed. Critically ill patients with severe pneumonia admitted to RICU were consecutively reviewed from March 2017 to October 2019. Chi-square test, Wilcoxon test, Mann Whitney U-test, Kaplan–Meier survival analysis or Cox’s proportional hazards regression model was used as appropriate. Results: A total of 72 eligible patients were included in the final analysis, 51 of which received BAL performed by FOB. Serum levels of PCT in group received BAL is markedly increased at 24 hours after FOB (p<0.001). Forty-eight hours later, BAL group with decreased serum levels of PCT had less SOFA score and decreased mortality compared with those with increased serum levels of PCT. Furthermore, Kaplan-Meier analysis indicated that patients with decreased serum levels of PCT had improved survival rate during hospital (Breslow test, p=0.041). However, increased PCT after BAL was not an independent risk factor for in-hospital mortality (hazard ratio: 1.689, 95% CI[ 0.626 ,4.563], p=0.301). Conclusions: BAL performed by FOB increased serum levels of PCT. However, PCT levels decreased at 48 hours after BAL predicted a good prognosis of patients with severe pneumonia.